STUDI TENTANG STATUS GIZI PADA RUMAHTANGGA MISKINDAN TIDAK MISKIN - Riyadi, Hadi; Khomsan, Ali; S, Dadang; A, Faisal; S. Mudjajanto, Eddy (GIZI INDONESIA, 2006)
NUTRITIONAL STATUS OF POOR AND NON-POOR HOUSEHOLDSNutritional status is a body health condition of a person or a group of people resulting from the consumption, absorption, and utilization of nutrients in food. This study aimed to asses nutritional status of children under five years, husbands, and wives in highland and coastal areas. This study used a case control group design. Case was poor household while control group was nonpoor household. The collected data from poor and nonpoor and from the highland and coastol areas were compared. Weight was measured using digital bathscale and height uses microtoise. The results indicated that most husbands and wives were in normal category, less than 15% had low nutritional status. Prevalence of overweight occured more frequently in nonpoor households. The prevalence of nutritional problems of children under five was greater in poor households than that in nonpoor households. The children’s under five years old nutritional status were similiar in both boys and girls.Keywords: nutritional status, children, poverty